Applying Universal Design for Learning in Teaching English Vocabulary in Inclusive Elementary Education: A Qualitative Study - Sofiyani Nasution; Rahmah Fithriani (Faculty of Education and Teacher Training of UIN Palopo, 2026)
Inclusive education aims to provide equitable learning opportunities for all students, yet many Indonesian schools still face challenges in implementing inclusive English instruction. This study explores the implementation of Universal Design for Learning (UDL) in teaching English vocabulary in teaching English vocabulary in an inclusive elementary classroom at an elementary school in Medan, Indonesia. Guided by two research questions, employing a descriptive qualitative research design, the study involved one English teacher with three years of experience teaching in an inclusive classroom. The participant was selected through purposive sampling based on her experience in teaching students with diverse learning needs. Data were collected through classroom observations conducted across four meetings, semi-structured teacher interviews, and documentation of lesson plans and learning media. The data were analyzed thematically using Braun and Clarke’s (2006) framework to identify patterns related to the teacher’s instructional strategies and perceptions of UDL implementation. The findings indicate that the teacher implemented the three principles of UDL: multiple means of representation, engagement, and expression. The teacher combined visual, auditory, and contextual representations to support vocabulary understanding, used flexible and emotionally supportive activities to enhance student engagement, and provided varied forms of assessment to allow students to demonstrate their understanding. These strategies supported vocabulary comprehension and increased participation among students with diverse learning needs. The study highlights the practical potential of UDL as an instructional framework for improving vocabulary learning and fostering inclusive practices in inclusive elementary classroom.